A solution-processable bipolar diketopyrrolopyrrole molecule used as both electron donor and acceptor for efficient organic solar cells. Issue 5 (23rd December 2014) - Shi, Hangqi; Fu, Weifei; Shi, Minmin; Ling, Jun; Chen, Hongzheng
Abstract : A DPP molecule has appropriate energy levels and bipolar charge-transport properties for both donor and acceptor in OSCs. Abstract : A new diketopyrrolopyrrole derivative with appropriate energy levels and bipolar charge-transport properties is designed and synthesized. When this molecule is used as either electron donor or acceptor, the resulting organic solar cells both give the power conversion efficiencies over 3%.